Animal rights : opposing viewpoints - Rohr, Janelle, 1963- (San Diego, CA : Greenhaven Press, 1989)
Presents thirty-two articles debating the question of whether animals have rights.
Includes bibliographical references (p. 224-232).
Keywords: Animal rights; Animal welfare; Animals -- Treatment; Animal rights